Monetary policy and liquidity management with an endogenous interbank network - Luiz Carpizo; Timo Hiller (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2022)
This paper studies a central bank's optimal interest rate corridor choice in the presence of an endogenous interbank network. We first provide a characterization of the unique equilibrium of banks' liquidity holdings for any network of credit lines. Then, we endogenize the network and show that every equilibrium network is a complete coreperiphery graph. Central banks face the following trade-off. A narrower corridor implies more precise targeting of the interbank rate. But, when accounting for banks' endogenous linking decisions, a narrower corridor may lead to a sparser interbank network with higher aggregate liquidity holdings. This incurs an implicit cost, since these funds could be invested in the more productive illiquid asset instead. We solve for the optimal corridor width and provide a comparative statics analysis.
Keywords: E58; D85; G21; 330; Interbank Market; Network Formation; Optimal Corridor Rate